Media E-Scrapbook untuk Stimulasi Kreativitas Anak Kelompok B - Ni Luh Trisna Angreni; Didith Pramunditya Ambara (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Parental affection shown inappropriately can hinder or limit children's activities and movements, so that children cannot explore freely and develop their imagination and creativity. This research aims to determine the significant influence of using e-scrapbook media on the creativity of group B children. This type of research is a quasi-experiment with a non-equivalent control group design. The population in this study was all 42 children from Group B, Denpasar. The research sample was taken using a saturated sampling technique because all population members were used as samples. Group B2, consisting of 21 children, was selected as the experimental group, and Group B1, consisting of 21 children, was selected as the control group. The data collection method used is a non-test method, namely observation using an assessment instrument for children's work based on a creativity assessment rubric. This research uses descriptive statistical analysis and inferential statistics. The results of this study show that the average post-test score in the experimental group was 82.57, while in the control group, it was 63, with a maximum score of 100. The t-test results showed a significant difference in the creativity of children taught using e-scrapbook media and those taught using conventional learning. It was concluded that the use of e-scrapbook media had a significant effect on the creativity of group B children.